Pemanfaatan Pelayanan Kesehatan dan Persepsi dengan Kepatuhan Akseptor Keluarga Berencana (KB) pada Masa Pandemi COVID-19 - Fika Nuri Fathul Jannah; Dian Nur Adkhana Sari (Universitas Ahmad Dahlan, 2022)
Background: The COVID-19 pandemic has had an impact on family planning programs. The government has made a new policy to limit family planning services during the COVID-19 pandemic. As a result, there is a decrease in family planning participation, causing a high risk of an increase in the number of pregnancies and an explosion in the birth rate. Utilization of health services and a good perception of family planning can increase the compliance of family planning acceptors. Objective: This study aims to determine the relationship between the utilization of health services and perceptions with the compliance of family planning acceptors during the COVID-19 pandemic at the Kalasan Health Center, Sleman. Methods: This research method is quantitative with a cross sectional approach. The population in this study were all family planning acceptors at the Kalasan Sleman Health Center with a total of 60 respondents. The sampling technique used was Total Sampling with a total of 53 respondents. Data analysis using Chi Square statistical test and multiple linear regression. Results: Based on the results of the Chi Square test, the variable of utilization of health services and compliance with family planning acceptors, the value of = 0.781 means that the value of >0.05 with multiple linear regression results Sig. 0.728. The results of the Chi Square test of the perception variable with the compliance of family planning acceptors obtained the value of = 0.318, meaning that the value of >0.05 with multiple linear regression values of Sig. 0.452. Conclusion: There is no significant relationship between the utilization of health services and perceptions of compliance with family planning acceptors during the COVID-19 pandemic at the Kalasan Health Center, Sleman Yogyakarta.